Phenotypic and genotypic analysis of bio-serotypes of Yersinia enterocolitica from various sources in Brazil - Rusak, Leonardo Alves; dos Reis, Cristhiane Moura Falavina; Barbosa, André Victor; Santos, André Felipe Mercês; Paixão, Renata; Hofer, Ernesto; Vallim, Deyse Christina; Asensi, Marise Dutra (The Journal of Infection in Developing Countries, 2014)
Introduction: Yersinia enterocolitica is a well-known foodborne pathogen widely distributed in nature with high public health relevance, especially in Europe. Methodology: This study aimed to analyze the pathogenic potential of Y. enterocolitica isolated strains from human, animal, food, and environmental sources and from different regions of Brazil by detecting virulence genes inv, ail, ystA, and virF through polymerase chain reaction (PCR), phenotypic tests, and antimicrobial susceptibility analysis. Pulsed-field gel electrophoresis (PFGE) was used for the assessment of phylogenetic diversity. Results: All virulence genes were detected in 11/60 (18%) strains of serotype O:3, biotype 4 isolated from human and animal sources. Ten human strains (4/O:3) presented three chromosomal virulence genes, and nine strains of biotype 1A presented the inv gene. Six (10%) strains were resistant to sulfamethoxazole-trimethoprim, seven (12%) to tetracycline, and one (2%) to amikacin, all of which are used to treat yersiniosis. AMP-CEF-SXT was the predominant resistance profile. PFGE analysis revealed 36 unique pulsotypes, grouped into nine clusters (A to I) with similarity ≥ 85%, generating a diversity discriminatory index of 0.957. Cluster A comprised all bio-serotype 4/O:3 strains isolated from animal and humans sources. Conclusions: This study shows the existence of strains with the same genotypic profiles, bearing all virulence genes, from human and animal sources, circulating among several Brazilian states. This supports the hypothesis that swine is likely to serve as a main element in Y. enterocolitica transmission to humans in Brazil, and it could become a potential threat to public health as in Europe.